EXPERT CONSENSUS: DISSECTING BULLYING ATTRIBUTES IN KLANG VALLEY SCHOOLS, MALAYSIA - Chua , Soo Sien; Kuek, Florence; Ching , Thing Ho (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Bullying remains a significant global concern that negatively affects the psychological, emotional, and social well-being of students. This leads to psychological distress, low self-esteem and an increased risk of suicidal ideation among adolescents in Malaysia. Despite growing awareness of bullying, the prevalence of bullying continues to rise, which highlights the need for a deeper understanding of its underlying determinants. This study aims to identify and prioritise the key determinants of bullying among Malaysian primary and secondary school students. A qualitative exploratory design employing the Nominal Group Technique (NGT) was utilised to systematically identify and prioritise expert consensus on bullying determinants in school. Data were collected from five experienced school counsellors with over 15 years of professional practice in the Klang Valley. Structured NGT sessions were conducted to elicit, discuss and rank the most significant contributing factors of bullying behaviour. The findings reveal seven key determinants of bullying behaviour, which are mental health, family dynamics, peer pressure with social dynamics, educational environment, insufficient awareness, inadequate character education, and social media influence, prioritised as the core seven determinants of bullying factors in primary and secondary schools in Klang Valley. This study contributes to the existing literature by providing empirical evidence grounded in expert ecological insights on the contextual determinants of bullying within the Malaysian educational context. This empirical context offers a prioritised, targeted prevention framework and practical intervention strategies for policymakers, educators, and parents to develop effective anti-bullying policies and programmes.